Microplastics in Commercially Important Small Pelagic Fish Species From South Africa - Bakir, Adil; van der Lingen, Carl D.; Preston-Whyte, Fiona; Bali, Ashok; Geja, Yonela; Barry, Jon; Mdazuka, Yandiswa; Mooi, Gcobani; Doran, Denise; Tooley, Freya; Harmer, Rogan; Maes, Thomas (Frontiers in Marine Science, 2020)
This study documented the levels of microplastics in three commercially important small pelagic fish species in South African waters, namely European anchovy (Engraulis encrasicolus), West Coast round herring (Etrumeus whiteheadi) and South African sardine (Sardinops sagax). Data suggested variation between species with a higher concentration of microplastics for S. sagax (mean of 1.58 items individual-1) compared to Et. whiteheadi (1.38 items individual-1) and En. encrasicolus (1.13 items individual-1). The occurrence of microplastics was also higher for S. sagax (72%) and Et. whiteheadi (72%) compared to En. encrasicolus (57%). Microfibres accounted for 80% of ingested microplastics (the remainder were plastic fragments) with the main ingested polymers being poly(ethylene:propylene:diene) (33% occurrence), polyethylene (20%), polyamide (20%), polyester (20%) and polypropylene (7%). The abundance of ingested items was not significantly correlated with fish caudal length or body weight, and spatial investigation indicated an increase in the abundance of ingested items from the West to the South coast. Etrumeus whiteheadi is proposed as a bio-indicator for microplastics for South Africa.